2019
DOI: 10.1017/hpl.2019.34
|View full text |Cite
|
Sign up to set email alerts
|

Effect of rear surface fields on hot, refluxing and escaping electron populations via numerical simulations

Abstract: After a population of laser-driven hot electrons traverses a limited thickness solid target, these electrons will encounter the rear surface, creating TV/m fields that heavily influence the subsequent hot-electron propagation. Electrons that fail to overcome the electrostatic potential reflux back into the target. Those electrons that do overcome the field will escape the target. Here, using the particle-in-cell (PIC) code EPOCH and particle tracking of a large population of macro-particles, we investigate the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(17 citation statements)
references
References 38 publications
0
17
0
Order By: Relevance
“…Moreover, a relatively small proportion of the electrons are accelerated to energies much above the average and may leave the target [28] , thus charging it positively. The total number of escaping electrons is defined by dynamical competition between the high energy of escaping electrons and the electric potential increase due to electron escape [29] . We describe numerical methods for the charge evaluation in Sections 2.3 and 2.4.…”
Section: Target Polarizationmentioning
confidence: 99%
“…Moreover, a relatively small proportion of the electrons are accelerated to energies much above the average and may leave the target [28] , thus charging it positively. The total number of escaping electrons is defined by dynamical competition between the high energy of escaping electrons and the electric potential increase due to electron escape [29] . We describe numerical methods for the charge evaluation in Sections 2.3 and 2.4.…”
Section: Target Polarizationmentioning
confidence: 99%
“…The measured electron distributions presented throughout this paper represent the escaping electron population, which is distinct from the internal electron distribution of electrons trapped within the target. Although, previous work [36][37][38] has demonstrated these two distributions to be linked.…”
Section: Resultsmentioning
confidence: 92%
“…An example of the latter is that the investigation into the effect of the electronic sheath field, responsible for ion acceleration, on fast electron dynamics within foil targets is reported in Ref. [7]. In that paper, it is shown that energetic electrons that do not overcome the electrostatic potential formed at the target rear are reflected and reflux within the foil.…”
Section: Scientific Highlights Through Publications In Hplsementioning
confidence: 99%